2002
DOI: 10.1111/j.1540-8183.2002.tb01073.x
|View full text |Cite
|
Sign up to set email alerts
|

Different Techniques for Closure of Multiple Interatrial Communications with the Amplatzer Septal Occluder

Abstract: We present three cases of multiple interatrial communications to illustrate the extended use of the Amplatzer septal occluder and to highlight procedural techniques. The first case demonstrates how a single device can be used to close two adjacent defects. It is important to balloon size both defects and to note if balloon occlusion of one defect closes the other and vice versa. The second case demonstrates closure of multiple atrial septal defects using two devices. The technique needed to obtain an "interlea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 8 publications
1
25
0
Order By: Relevance
“…Implantation of multiple devices was required in about half of the cases, especially in patients with d-ASD and c-ASD, and was performed by using the same procedure, applying the standard technique in all cases. A minimum distance of 5 mm among defects and deploying of the smaller device first are the key elements to assure correct positioning and complete opening of all devices [9][10][11][12][13]. In particularly complex anatomy, the association of a selfcentering device (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Implantation of multiple devices was required in about half of the cases, especially in patients with d-ASD and c-ASD, and was performed by using the same procedure, applying the standard technique in all cases. A minimum distance of 5 mm among defects and deploying of the smaller device first are the key elements to assure correct positioning and complete opening of all devices [9][10][11][12][13]. In particularly complex anatomy, the association of a selfcentering device (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Data about the feasibility and efficacy of using transcatheter approach to close the multiple ASDs are limited [3][4][5][6][7][8]. Cao et al [3] and Butera [4] reported the clinical result of percutaneous closure of multiple ASDs and provided initial experience of device closure for this type of ASD.…”
Section: Discussionmentioning
confidence: 96%
“…However, only limited studies have tried to examine the feasibility and effectiveness of using transcatheter closure for patients with multiple ASDs using multiple devices [3][4][5][6][7][8]. Presenting with various morphologies, those defects are often difficult to close via transcatheter approach in technical aspect [3,5,8].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…While these authors were successful in occluding the defect, I am not in favor of using such a technique. A large single Amplatzer device may be deployed in the larger defect to occlude two or more smaller defects as used by and others (Roman et al 2002). While examining this technique, Szkutnik et al (2004) found that a smaller defect less than 7 mm distance from the larger defect had a 100% closure rate at 1 month follow-up.…”
Section: Multiple or Fenestrated Defectsmentioning
confidence: 98%